PROSES PELAYANAN PUBLIK IZIN MENDIRIKAN BANGUNAN (IMB) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) DI KABUPATEN SIAK - ", Khairunisa; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of this policy regarding IMB needs special attention by the Siak Regency  Government, the number of buildings that do not have an IMB occurs due to factors such as lack of public knowledge about IMB, difficulties in managing it, as well as costs that are felt to be too expensive to take care of permits. The aims of this research are: (1) To find out how the issuance of Building Construction Permits (IMB) at the Office of Investment and One Stop Integrated Services (DPMPTSP) in Siak Regency in 2018 and (2) To determine the quality of public services in the issuance of Building Construction Permits (IMB) based on the dimensions tangible, reliability, responsiveness, assurance and empathy at the One Stop Integrated Service and Investment Service (DPMPTSP) in Siak Regency).The theory used in this study is the theory of the determinants of the quality of public services according to Parasuraman et al, which consists of tangible, reliability, responsiveness, assurance and empathy. Data collection techniques used in this study  were  interviews and documentation. This research was conducted at the Office of Investment and One Stop Integrated Services (DPMPTSP) in Siak Regency.The results of this study indicate that the existence of standard operating procedures for services that have been regulated in the provisions of the legislation has provided a guarantee of timeliness of service, legality of services and determination of service fees / tariffs submitted by operator officers can give confidence to the applicant to process the IMB application. Keywords:      Building Construction Permit (IMB), Public Service Study, Siak Regency DPMPTSP